MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KEqEPATAN ABSTRACT PEMBUATAN PINTU KAYU - -, Didik Nurhadiyanto; S, Suprapto Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
Inmakingwoodcraftingspeciallymakingof door andshutter leaf oftentimesobtaineda handicappeddoor productat shares penholein the formof barst / break,thedifficultymakethedoorleafifmarket requestquitea lot,and narrowtightworkplaceSothat neededa workbenchwhichmuliti functionso that allworkabledoormakingworkthedesk.Consideringproblemsfacedby this wood industryhencetheindustryrequiretobe assistedbygivena applianceofdoor maker inthelbnnof aworkbenchof multifunction providedby theapplianceofholepenmaker.Withtheworkbenchall workercan finishthe workof doormaking startfrom cuttingr.rfworkpiece.making of holepencomeup with thesetting.The aim ofthisprogramis toperformandmaketheworkbenchby meansof holepento increasequalityand timeefficiency,so thatsmallindustrycan do themoreorder.Inexecutingthis prograrnwe takethe followingstages :(l)planningworkbenchtoproducethe leafofdoor or window,matchingwithsociety condition.Sothat thisapplianceeasyto acceptedby society hencethis applianceown thefollowingspecification:Easy tooperate it,economizethe place,workof makingof'door leafbecomeeasier,(2)testingworkbenchto makedoorinwoodindustryindustry"UD.WARSIDI"toknowuntil wherethe applianceperformace,covering istamenityandspeedfinishthe makingof doorleaf.(3)door leafyieldedfrornthisappliancecomparedto by itsqualitywiththe doorleaf madeconventionally.(4 )machinecompletionitsperformanceaccordingtoplan (5)deliveringthemachine atpartnerindustrytobe utilizedso thatcanbeproductive.(6)compiling finalreport ofactivityexecution.Result ofinferentialworkbench perfomancetest-driveas follows :(1)Makerofholepenof thisdesk canfunctionbetter.Holediameter chiselbetween9up to l5mm.(2)Comperedto workmanshipinconventionallymakingof holepenwiththisdesk isquickertill4times.(3)deskcanbe usedbLtter to ieapthe sidegoodness stepasideandalso wideside.(4) longdeskof the size2.03m, wideo,g4 m,high0,71m,speedturnaroundthemotor is2.800rpm, speedturn aroundto drill2.800rpm,(5)withthis workbench,during2 daycanmake8 shutterand 2 doorleafwhereaswithoutusingworkbenchonly canmake5 shutterandI door leaft(6)qualityof resultof workinmakingsofterhotepenwhencomparedto a manualwork(?)efficiencyofplaceuseveryhigh.'Key *) word: workbench,hole pen,door,andwindow